Odpowiedzi

2010-03-24T17:06:01+01:00
E) 3 - 3x - 1 + 2x = 9
-x = 9 - 3 + 1
-x = 7 //: (-1)
x = -7

a) 12y - y - 5 = 10y - 1
11y - 10y = 5 - 1
y = 4

b) 2u - 10 + 15 = 3u - 12 +10
-u = -7 //:(-1)
u = 7
1 5 1
2010-03-24T17:06:17+01:00
Zad. 7 str. 164
Rozwiąż równanie.
e) 3(1-x)-(1-2x)=9
3-3x-x+2x=9
-3x-x+2x=9-3
-2x=6/: (-2)
x=-3

zad. 8 str. 164
Rozwiąż równanie.
a) 12y-(y+5)=10y-1
12y-y-5=10y-1
12y-y-10y=-1+5
y = 4

b) 2(u-5)+15=3(u-4)+10
2u-10+15=3u-12+10
2u-3u=-12+10+10-15
-u = -7 / :(-1)
u=7
3 4 3
2010-03-24T17:08:08+01:00
E) 3(1-x)-(1-2x)=9
3-3x-1+2x=9
-x=9-2
-x=7 /*(-1)
x=-7
8.
a)
12y-(y+5)=10y-1
12y-y-5=10y-1
11y-10y=-1+5
y=4
b)
2(u-5)+15=3(u-4)+10
2u-10+15=3u-12+10
2u-3u=-2-5
-u=-7 /*(-1)
u=7
1 5 1